PERAN PEMUDA DALAM PENGELOLAAN SAMPAH DI KOTA PEKANBARU (STUDI KASUS KOMUNITAS SOSICAL CORNER) - Arbi Rahayudi; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Social Corner being the community that have main focus on community empowerment and environmental. The goal of this study is to know the role and capital that attached in Social Corner Community. Using the qualitative approach, the author chooses the informants purposively consist of director and community member. This study found that the main principle of Social Corner in carrying out activities is the development of partnership networks with cross-sectoral both fellow communities who pay attention to the same or different issues as well as government and private element. The activities based on partnership and what the community does itself, such as waste volunteers, community assistance, and hygiene campaigns can provide benefits to the community. This benchmark can be seen from the award that giving by Pekanbaru government to Social Corner as youth community of city pioneers worthy of Pekanbaru in 2019. Meanwhile the most powerful and prominent formof social capital is from social networks that can be form and maintained as the main base of community activities. The weakest element lies on member’s commitment to agreed norms in the form of AD/ART. Not all members following that regulations, because most of them are students who have activities outside the community. Nevertheless the members with low commitment is not penalized, because all of decisions are made on the principle of kinship and flexible tolerance. Keyword: Community, Environment, Empowerment, Social